Formulation and Evaluation of Mesalamine Nanosphere Tablet - Pachpute, Tejas; Dwivedi, Jayesh; Shelke, Tushar; Jeyabalan, G. (Journal of Drug Delivery and Therapeutics, 2019)
Nanospheres are the particles having the size range between 10-200 nm in diameter. Nanospheres can be amorphous or crystalline in nature and also they have the ability to protect the drug from enzymatic and chemical degradation. For the preparation of standard calibration curve of Mesalamine with Phosphate buffer pH 6.8 and Absorbance of µg/ml solution was measured between 200-400nm by using Shimadzu 1601 UV/Vis double beam spectrophotometer. Nanosphare containing Mesalamine were prepared using nanoprecipitation method. 200 mg of polymer (Eudragit RS and L) was dissolve in 50 ml water. Drug was dissolve in 20 ml of methanol. Both solution were mixed and add 50 ml of water and stirred for half an hour. Methanol and water was evaporated under reduced pressure using rotary flash evaporator until 10 ml of solution was remaining. Than this suspension was centrifuge at 15000 rpm at 40C for half an hour. The supernatant was discarded and remaining portion was washed with distilled water. The nano-sphares was dried over night at 600C and stored in desiccators. The surface morphology (roundness, smoothness, and formation of aggregates) and particle size was studied by scanning electron microscopy (SEM). Zeta potential of the best formulation (F4) was determined by zeta potential probe model DT- 300. Mesalamimne, Dextrose and Lactose were taken in required quantities mixed and granulating agent (Starch past) was added and passed through #40 sieves, then lubricant magnesium stearate and talc was added then compressed into tablets by rotary tablet punching machine. Then film coating is done by 6% w/v solution of Cellulose acetate Phthalate in isopropyl alcohol using 2% tween-80 as plasticizer in coating pan. The weight of tablet was kept constant for all formulations. Nanosphare tablet formulation F-2 Showed maximum drug (97.75%) released and formulation F-4 showed 92.58% drug release. The In-vitro drug released study result showed that formulation F-2 96.58% drug was released after 17 hours which is highest drug release amongst all other tablet formulation.